The Newest Medications in Kidney Transplantation and their Mechanisms of Action - Lesan Pezeshki, Mahboob (Urology Journal, 2009)
Purpose: In recent years, many new immunosuppressive drugs have been discovered and developed for clinical use in transplantation. This review focuses on new drugs and novel strategies that have been shown to have immunosuppressive activity in patients. Materials and Methods: The literature was reviewed. Results: The introduction of cyclosporine in the early 1980s improved renal allograft survival by approximately 15 percent at one year post transplant. However, cyclosporine failed to enhance long term graft survival. In addition, transplant recipients are at risk of significant side effects due to immunosuppression, including infection, cardiovascular disease, hypertension and malignancy. The limitations constitute the rational for the continued development of new immunosuppressive agents. Conclusion: The therapeutic armamentarium for transplant immunosuppression continues to broaden and become more complex, as does the variety of potential drug combinations or protocols. Further studies in a large number of individuals are required to clarify the role of new immunosuppressive agents and novel strategies in transplant recipients.